GLONASS Observation of Artificial Field‐Aligned Plasma Irregularities Near Magnetic Zenith During EISCAT HF Experiment - Sato, H.; Rietveld, M. T.; Jakowski, N. (FID GEO, 2021)
We report on simultaneous observation of artificial plasma density irregularities near the magnetic zenith (MZ) by incoherent scatter radar and GNSS satellite in the high latitude. During an EISCAT (European Incoherent Scatter Scientific Association) HF heating experiment, a GLONASS satellite signal intersected the disturbed ionospheric volume along the local magnetic field lines. The satellite signal amplitude and phase were simultaneously perturbed when the electron temperature increased in the F region through O‐mode HF waves. The field‐aligned irregularities (FAIs) and associated density perturbations are most significantly found in the MZ direction. The growth of FAI reached the saturation level in 30 s while large‐scale electron density perturbation on the order of 0.1 TECU developed in a few minutes. The observed density perturbations agree well with recent numerical studies of FAI generation due to the thermal self‐focusing process. : Plain Language Summary: Powerful high‐frequency radio waves are used to study electron heating process in the high latitude ionosphere. We observed the development of plasma density structures by analyzing small changes of amplitude and phase of ground‐based satellite signals and incoherent scatter radar measurements. It is concluded that the electron heating causes irregular electron density structures along local magnetic field lines. This experiment shows that coordinated ground‐based satellite and incoherent scatter radar measurements essentially help to better understand the physics of ionospheric plasma dynamics and radio wave propagation. : Key Points: HF‐induced field‐aligned plasma irregularities are simultaneously observed by GLONASS satellite and incoherent scatter radar. The satellite signal amplitude fluctuation and TEC deviation are generally correlated. Observed positive density deviations suggest that the density perturbations are likely caused by the thermal self‐focusing process.